2021
DOI: 10.3389/fpsyg.2021.671407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Quality Perceived of Service of a Higher Education Center on the Loyalty of Students

Abstract: The aim of this research is to validate the explanatory model of how the quality of service perceived by students of a higher education center influences their loyalty (retaining and attracting new students) through mediating variables: perceived value, expectations, and satisfaction. The methodology used to validate the measurement scales is exploratory, and confirmatory factor analysis and the structural equation modeling (SEM) technique are applied to analyze the causal relationships proposed in the model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 109 publications
(172 reference statements)
4
20
0
Order By: Relevance
“…Similar to previous research findings, increased satisfaction was associated with increased loyalty ( Sirdeshmukh et al, 2002 ; Ling and Ding, 2006 ; Han et al, 2021 ). This was similar to findings in the field of education, where higher parental satisfaction was associated with increased loyalty to school ( Leventhal et al, 2006 ; Chen, 2013 ; Budiyanto et al, 2021 ; Río-Rama et al, 2021 ). Thus, we reveal this positive relationship in the context of preschool education, which echoes previous research findings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to previous research findings, increased satisfaction was associated with increased loyalty ( Sirdeshmukh et al, 2002 ; Ling and Ding, 2006 ; Han et al, 2021 ). This was similar to findings in the field of education, where higher parental satisfaction was associated with increased loyalty to school ( Leventhal et al, 2006 ; Chen, 2013 ; Budiyanto et al, 2021 ; Río-Rama et al, 2021 ). Thus, we reveal this positive relationship in the context of preschool education, which echoes previous research findings.…”
Section: Discussionsupporting
confidence: 86%
“…This means that the more satisfied parents are, the more likely they are to keep their children in school. Previous empirical studies have found that satisfaction has a significant and positive effect on loyalty ( Cabello-Manrique et al, 2021 ; Han et al, 2021 ; Río-Rama et al, 2021 ). Budiyanto et al (2021) showed that parental satisfaction had a significant and positive effect on parental loyalty.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Though it is well established that positive perceptions of service quality can have a significant impact on students' satisfaction (Annamdevula & Bellamkonda, 2016), the debate over how to define service quality in the context of higher education continues. As a result, there is no agreement on "the best way to define and measure service quality" (Ro-Rama, de la Cruz, lvarez-Garca, Mun, & Durán-Sánchez, 2021). In this study, service quality in higher education is defined as the gap between what a student expects and his or her perceptions of actual delivery.…”
Section: Concept Of Service Deliverymentioning
confidence: 95%
“…Some observers suggest that student-customer satisfaction is directly influenced by their expectation of the choice factors (Patterson & Johnson, 1993;Voss et al, 2007). Najimdeen et al (2021) argue that student-customer expectation indirectly influences customer satisfaction in service quality, whereas other scholars find a direct relationship between student customer expectation and customer satisfaction (Río-Rama et al, 2021). Tukiran et al (2021) conclude that student expectations may, directly and indirectly, impact satisfaction.…”
Section: Factors Affecting Student Expectations-satisfactionmentioning
confidence: 99%